Micronutrientes em perfis de solos do Escudo Sul-riograndense. - Silva, Juliana Brito da (2009)
The highlands from the southern region of State of Rio Grande do Sul have been traditionally used for extensive cattle raising, which practically does not demand soil analysis and fertilization. The sustainable use of the soils with other agricultural activities, such as forestry, that has been increased in the last few years, needs a more suitable and accurate knowledge of the needs of soil fertilization, including the micronutrients. In this context, this study has the objective of quantifying the micronutrients availability and reserve present in the different types of soils of the region. For this purpose, 22 soil profiles representative of the different soil parent material and profile development found in the region were sampled and chemical analysis of the total, available and oxide bound Cu, Zn, B, Fe and Mn were performed. The results indicate that for the majority of the soils the available and total contents of micronutrients are high, with more likely deficiency possibilities for Cu and B, in this order, related to specific soil parent material types. For Zn and Mn, despite the high available contents, there is the possibility of deficiency in the future due to a low reserve in case the crop withdraw be not returned. The ammonium oxalate extracted Cu and Zn data indicate that the reserve of these micronutrients in low cristallinity Fe (and Mn) is negligible. Only a small fraction of the total Cu is found in oxides in the soils studied, in opposition to the Zn, where in a topsoil it reached around 65%.